Analisis Digital Marketing Terhadap Keputusan Pembelian Konsumen di Era Modern - Mustika Via Baharsah; Munawaroh Munawaroh (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
Digital marketing has become one of the main approaches in modern marketing strategies, especially with the rapid development of information and communication technology. In the modern era, consumer behavior has undergone a significant transformation, where purchasing decisions are increasingly influenced by information available online. Social media has a dominant role in building interactions between consumers and brands, while SEO and content marketing contribute to increasing brand awareness and purchasing decisions. In addition, personal and relevant digital advertising has been shown to increase conversion rates, while email marketing has a more significant impact on maintaining customer loyalty. Factors such as brand trust, the quality of information presented, and the overall user experience have also been found to have a significant influence on consumer purchasing decisions. Digital marketing not only functions as a promotional tool, but also as a means to build closer relationships with consumers, increase engagement, and create a more personalized purchasing experience.